Comparing the use of modern and traditional building design systems in construction projects - Nassar, Yasser Sahib (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Any construction project through several stages, starting from the feasibility study stage to the project delivery stage, as the most critical stage that must be focused on is the design stage. It was essential to adopt modern and advanced programs at the design stage to avoid problems and claims between the employer and the contractor due to changes and errors that occur in the project—design process. BIM is one of the modern technologies with many benefits that can be used to solve these errors and obstacles. This research aims to clarify the effectiveness of introducing the BIM system in the design stage of the construction building by comparing it with traditional CAD systems. In this research, ten different actual projects were studied in the architectural design stage to be used in the comparison process between BIM and CAD systems. The researcher reached a set of results, including that introducing the (BIM) in the architectural and structural design stage can reduce the time required to produce design documents by up to (67.6%). This study is helpful for all governmental and private design companies and encourages decision-makers to use the BIM system.